The Causal Evidence of Birth Weight and Female-Related Traits and Diseases: A Two-Sample Mendelian Randomization Analysis - He, Renke; Liu, Rui; Wu, Haiyan; Yu, Jiaen; Jiang, Zhaoying; Huang, Hefeng (Frontiers in Genetics, 2022)
Objectives: A large meta-analysis indicated a more pronounced association between lower birth weight (BW) and diseases in women but less concern about the causality between BW and female-related phenotypes and diseases. Methods: Mendelian randomization (MR) analysis was used to estimate the causal relationship between two traits or diseases using summary datasets from genome-wide association studies. Exposure instrumental variables are variants that are strongly associated with traits and are tested using four different statistical methods, including the inverse variance weighting, MR-Egger, weighted median, and weighted mode in MR analysis. Next, sensitivity analysis and horizontal pleiotropy were assessed using leave-one-out and MR-PRESSO packages. Results: The body mass index (BMI) in adulthood was determined by BW (corrected β = 0.071, p = 3.19E-03). Lower BW could decrease the adult sex hormone-binding globulin (SHBG) level (β = −0.081, p = 2.08E-06), but it resulted in increased levels of bioavailable testosterone (bio-T) (β = 0.105, p = 1.25E-05). A potential inverse effect was observed between BW and menarche (corrected β = −0.048, p = 4.75E-03), and no causal association was confirmed between BW and the risk of endometriosis, leiomyoma, and polycystic ovary syndrome. Conclusion: Our results suggest that BW may play an important role and demonstrates a significant direct influence on female BMI, SHBG and bio-T levels, and menarche.